Social competence and its relation to academic achievement among primary and middle school students - ben nouioua, djamel (Journal of Social Sciences and Humanities, 2020)
This research aims to study the social competence and its relationship to academic achievement primary and Secondaryschool, where the descriptive approach was used in order to measure the level of social competence and reveal the differences between students in primary and Secondary schoolin the level of social competence according to theirgender and reveal the relationship of the level of social competence to academic achievement, and the study sample consisted Of 66 students randomly chosen from among all primary and intermediate students in the wilaya msila, the scales used in this study was the measure of social competence, which is a sub-measures of School Social Behavior Scale(ssbs) by Kenneth W. Merrell (1993) .The scale divided into three dimensions (personal social skills -self-control skills -academic skills). We also confirmed the Validity of the scale in terms of internal consistency and discriminatory honesty. As for Reliability, it was with an alpha Cronbach coefficient of 0.96 for the scale as a whole, and for sub-measures between 0.88-0.93, which shows that the applied scale is characterized by high Reliability and Validity The results for the first question about the level ofsocial competence of the students were high, As for the second question about the relationship of social competence and academic achievement, we obtained a high Pearson coefficient value (0.91) which indicates the strength of the relational relationship. As for the third question, there are no statistically significant differences for the mean scores of the social competency scale attributed to the gender variable.